A review on fire suppression by fire sprinklers. (November 2021) - Abdulrahman, Shehu A; Chetehouna, Khaled; Cablé, Axel; Skreiberg, Øyvind; Kadoche, Maurice
Water spray remains the most effective, environment-friendly and economical way of fighting accidental or unwanted fires, and this is largely due to its thermal characteristics. The mechanism of fire suppression by sprinkler water sprays is influenced by numerous factors, which have been the focus of years'-long and on-going research studies to improve its extinguishing performances. A comprehensive review study was carried out in this study to assess the level of technological know-how and current state of research in the field. A total of 2473 published articles spanning 50 years (i.e. 1970–2020) were systematically collected and analysed, whereby more than 100 relevant articles were selected and integrated in the discussion. In particular, the review focuses on research relating to the interactions of sprinkler sprays with flame, fire plume and hot surfaces, aiming to provide a better understanding of the phenomena involved in fire suppression.